Detection of Antibodies to Lokern, Main Drain, St. Louis Encephalitis, and West Nile Viruses in Vertebrate Animals in Chihuahua, Guerrero, and Michoacán, México - Garza Hernandez, Javier Alfonso (2021)
We conducted serologic surveillance for flaviviruses and orthobunyaviruses in vertebrate animals in Mexico in 2018–2019. Sera were collected from 856 vertebrate animals, including 323 dogs, 223 horses, and 121 cows, from 16 species. The animals were from 3 states: Chihuahua in northwest Mexico (704 animals) and Guerrero and Michoacan on the Pacific Coast (27 and 125 animals, respectively). Sera were assayed by plaque reduction neutralization test using four flaviviruses (dengue type 2, St. Louis encephalitis, West Nile, and Zika viruses) and six orthobunyaviruses from the Bunyamwera (BUN) serogroup (Cache Valley, Lokern, Main Drain, Northway, Potosi, and Tensaw viruses). Antibodies to West Nile virus (WNV) were detected in 154 animals of 9 species, including 89 (39.9%) horses, 3 (21.4%) Indian peafowl, and 41 (12.7%) dogs. Antibodies to St. Louis encephalitis virus (SLEV) were detected in seven animals, including three (0.9%) dogs. Antibodies to Lokern virus (LOKV) were detected in 22 animals: 19 (8.5%) horses, 2 (1.7%) cows, and a dog (0.3%). Antibodies to Main Drain virus (MDV) were detected in three (1.3%) horses. WNV and LOKV activity was detected in all three states, SLEV activity was detected in Chihuahua and Michoacan, and MDV activity was detected in Chihuahua. None of the animals was seropositive for Cache Valley virus, the most common and widely distributed BUN serogroup virus in North America. In conclusion, we provide serologic evidence that select flaviviruses and BUN serogroup viruses infect vertebrate animals in Chihuahua, Guerrero, and Michoacan. We also provide the first evidence of LOKV and MDV activity in Mexico.